Pengaruh Iklim Organisasi, Lingkungan Kerja Fisik dan Lingkungan Kerja Non Fisik Terhadap Kinerja Pegawai: Studi Pada Pegawai Kantor KPU dan Bawaslu Kabupaten Ciamis - Yulian Nisa; Enas Enas; Ferey Herman (Universitas 45 Surabaya, 2024)
In an organization, performance can be influenced by the work environment and organizational climate. Organizational performance is greatly influenced by the organizational climate and work environment, both physical and non-physical. To encourage employees to be more responsible and focused on their work, an organization must always pay attention to and be able to create a pleasant, comfortable and safe work atmosphere. Based on initial observations, the problems at the KPU and Bawaslu offices in Ciamis Regency are that there are still delays in completing work, inadequate infrastructure, and so on. This can result in hampered employee performance. The method used in this research is a quantitative method. The research results are as follows: 1). Employee performance is influenced positively and significantly by organizational climate. This means that the higher the employee's performance, the better the organizational climate will be. On the other hand, the performance of employees at the KPU and Bawaslu offices in Ciamis Regency will be disrupted if the organizational climate worsens. 2). Employee performance is influenced positively but not significantly by the physical work environment. 3). Employee performance is influenced positively and significantly by the non-physical work environment. 4). The physical and non-physical work environment, as well as the organizational climate, all influence employee performance positively and significantly.